EDUKASI DAN PEMERIKSAAN KADAR GULA DARAH (KGD) SEBAGAI UPAYA DALAM MENINGKATKAN PENGETAHUAN MASYARAKAT DI DESA SEI BELUTU KECAMATAN MEDAN SUNGGAL - Ariyanti, Ika; Fentiana, Nina; Putra, Pratama; Jadimanto, Jadimanto; Cindy, Cindy (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Diabetes mellitus is a chronic disease characterized by high levels of sugar in the body, but which cannot be utilized properly by the body. This disease is also starting to spread to rural areas and can endanger the health of village communities, including Sei Belutu Village. The aim of this community service is to provide an understanding of the importance of prevention and complications of Diabetes Mellitus through education. The methods used in this community service include checking blood sugar levels and providing education to 30 elderly people in Sei Belutu village, Medan Sunggal District. The educational material consists of the definition, causes and risk factors, symptoms, various types, disease process, prevention and management of diabetes mellitus. Education is provided through lectures. Participants' knowledge was assessed using a written test before and after the education session. The results of the analysis showed that the level of knowledge of the community in Sei Belutu village before being given education was 17 people had poor knowledge and 13 people had good knowledge. After education, knowledge increased to good for 20 people, while 10 people still had poor knowledge about Diabetes Mellitus. Evaluation shows participants' activeness during educational activities. The conclusion from this community service is that education is able to increase knowledge about Diabetes Mellitus. It is recommended that education about Diabetes Mellitus be started early in productive age as a preventive measure before complications occur